Analysis of the Performance of Pharmacy Staff During Distribution of Medication Using the AHP and Rating Scale Method - Tobing, Madeline Angeline; Ginting, Chrismis Novalinda; Nasution, Ali Napiah (Journal La Medihealtico, 2023)
This research was conducted to determine the dimensions and indicators needed to assess the performance of pharmacy officers, determine the weight of each dimension and indicator using the Analytical Hierarchy Process (AHP) method and carry out performance assessments using the rating scale method. This type of research is quantitative descriptive research. The population in this study were 21 pharmacy officers who distributed medicine at Hermina Hospital in Medan. The sample used in this study used total sampling where the number of samples was the same as the population, so that the sample used was 21 pharmacy officers who distributed medicine at Hermina Hospital in Medan. The research results show that the factors used in assessing the performance of pharmacists when distributing medicine at Hermina Hospital in Medan in 2023 are work quality, presence, attitude, initiative, honesty and cooperation. The results of the performance assessment using the AHP method where the performance of pharmacy officers when distributing medicines at Hermina Hospital in Medan in 2023 were 4 people in the very good criteria, 5 people in the good criteria, 12 people in the medium criteria. In calculating the performance assessment of officers when distributing medicines using the rating scale method at Hermina Hospital in Medan in 2023, the priority work required when distributing medicines at Hermina Hospital in Medan in 2023 is collaboration and data results carried out by researchers which have the lowest influence on performance assessment. pharmacy officers during drug distribution at Hermina Hospital in Medan in 2023, namely the respondent's initiative.